2015
DOI: 10.1017/xps.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-Black Political Messages on Self-Esteem

Abstract: This study examines how anti-Black political rhetoric affects race-specific collective selfesteem (R-CSE) and internal political efficacy among African-Americans and Whites. Results from an experiment in which subjects received an anti-Black stereotype-accentuating message attributed to either a political figure or an "ordinary American," or no message at all, demonstrate that the political message undermined how African-Americans regard their own racial group, activated beliefs about how others regard African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As a result, those who belong to stigmatized groups employ various strategies to deal with and respond to potential identity threats. Importantly, these threats can be external to the group (Lyle 2015; Pérez 2015) or can be perceived as emerging from within—the consequence of individual group members’ behaviors or ways of being (Lewis and Sherman 2003; Taylor et al 2018).…”
Section: Respectability Politics As a Social Psychological Phenomenonmentioning
confidence: 99%
“…As a result, those who belong to stigmatized groups employ various strategies to deal with and respond to potential identity threats. Importantly, these threats can be external to the group (Lyle 2015; Pérez 2015) or can be perceived as emerging from within—the consequence of individual group members’ behaviors or ways of being (Lewis and Sherman 2003; Taylor et al 2018).…”
Section: Respectability Politics As a Social Psychological Phenomenonmentioning
confidence: 99%
“…We suggest that trans people might receive attention, honour and respect as a result of policy makers' positive actions aiming to support their workplace opportunities. Rawls (1971) suggested that without self-esteem nothing may seem worth doing, or if some things have value for people, they lack the will to strive to them (Lyle, 2015). People with higher self-esteem are more satisfied with their lives, have fewer interpersonal problems, achieve at a higher and more consistent level, and are less susceptible to psychological problems and physical illness than those with lower self-esteem (Lyle, 2015;Fernandez-Gonzalez et al, 2015;Karatepe and Demir, 2014;World Health Organization, 2014;Carter and Garber, 2011;Avison and McAlpine, 1992;Rosenberg and Pearlin, 1978;Rosenberg, 1965).…”
Section: Rawls Positive Actions and Trans People's Self-esteemmentioning
confidence: 99%